Antecedents of Cause Marketing: An Assessment of Psychographic and Demographic Factors on the Consumer's Purchase Behaviour. (December 2019) - Gupta, Shruti
Cause marketing initiatives are increasingly becoming the prominent aspect of the marketing mix; a lot of companies are jumping into the bandwagon primarily to distinguish themselves in the homogeneous markets. However, it is only a recent phenomenon that the companies are beginning to appreciate how corporate giving may be adopted as an effective strategy to market their products in the competitive markets. This article is aimed at examining the effect of psychographics and demographics on the buying behaviour of the consumer. It identifies the various factors that drive the behaviour of the consumer exposed to a customer relationship management (CRM) initiative and examine the impact of the same on the attitude, perception and purchase intention of the consumer. This, in turn, provides valuable insights to the academicians and the practitioners as to how to communicate and what to emphasise while designing their cause marketing communication initiatives.